Comparison of open and short-circuit switches faults voltage source inverter (VSI) analysis using time-frequency distributions - Manap, Mustafa; Ahmad, Nur Sumayyah; Abdullah, Abdul Rahim; Bahari, Norhazilina (Trans Tech Publications, 2015)
Power electronics are highly expanded area in industrial process which offers reliability, survivability and continuous operation. However, the emergence of switches fault has become a major concern in the development of advanced. Switches faults founded in VSI causing equipment failure and cost increased in manufacturing process. Therefore, the fault detection of voltage source inverter (VSI) is necessary to identify the VSI switches faults. This paper presents the analysis of VSI switches faults using TFDs which are short times fourier transform (STFT) and spectrogram. From time-frequency representation (TFR) obtained by using the TFDs, parameters of faults signal can be estimated such as instantaneous of average, RMS, Fundamental, Total Waveform Distortion (TWD), Total Harmonics Distortion (THD) and Total non-Harmonic Distortion (TnHD) of current signals. Based on the characteristics of the faults calculated from the signal parameters, VSI switches faults can be detected and identified. The performance of TFD for the faults analysis is also demonstrated to select the best TFD for switches faults detection and identification system.